A comparison of hydrogen release kinetics from 5- and 6-membered 1, 2-BN-cycloalkanes. Issue 54 (20th October 2021) - Giustra, Zachary X.; Chen, Gang; Vasiliu, Monica; Karkamkar, Abhijeet; Autrey, Tom; Dixon, David A.; Liu, Shih-Yuan
Abstract : The reaction order and Arrhenius activation parameters for spontaneous hydrogen release from cyclic amine boranes, i.e., BN-cycloalkanes, were determined for 1, 2-BN-cyclohexane (1 ) and 3-methyl-1, 2-BN-cyclopentane (2 ) in tetraglyme. Abstract : The reaction order and Arrhenius activation parameters for spontaneous hydrogen release from cyclic amine boranes, i.e., BN-cycloalkanes, were determined for 1, 2-BN-cyclohexane (1 ) and 3-methyl-1, 2-BN-cyclopentane (2 ) in tetraglyme. Computational analysis identified a mechanism involving catalytic substrate activation by a ring-opened form of 1 or 2 as being consistent with experimental observations.